Errors in Converting Principles to Protocols: Where the Bioethics of U.S. Covid‐19 Vaccine Allocation Went Wrong. Issue 5 (13th October 2022) - Parker, William F.; Persad, Govind; Peek, Monica E.
Abstract: For much of 2021, allocating the scarce supply of Covid‐19 vaccines was the world's most pressing bioethical challenge, and similar challenges may recur for novel therapies and future vaccines. In the United States, the Centers for Disease Control and Prevention's Advisory Committee on Immunization Practices (ACIP) identified three fundamental ethical principles to guide the process: maximize benefits, promote justice, and mitigate health inequities. We argue that critical components of the recommended protocol were internally inconsistent with these principles. Specifically, the ACIP violated its principles by recommending overly broad health care worker priority in phase 1a, using being at least seventy‐five years of age as the only criterion to identify individuals at high risk of death from Covid‐19 during phase 1b, failing to recommend place‐based vaccine distribution, and implicitly endorsing first‐come, first‐served allocation. More rigorous empirical work and the development of a complete ethical framework that recognizes trade‐offs between principles may have prevented these mistakes and saved lives .